Dynamic response characteristics of the shaft-blisk-casing system with blade-tip rubbing fault. (July 2021) - Zeng, Jin; Zhao, Chenguang; Ma, Hui; Cui, Xiaoli; Sun, Wei; Luo, Zhong
Highlights: Fully flexible modeling of shaft-blisk-casing system via beam-shell hybrid element. Improved disk-blade hybrid-dimensional interface coupling method. The law of spectrum feature, axis orbit, and phase diagram under blade-tip rubbing. Abstract: In this paper, the self-programmed spring-beam-shell hybrid element combined with the Lagrange multiplier method is utilized to establish the finite element model of a fully flexible shaft-blisk-casing system with blade-tip rubbing fault. Particularly, an improved disk-blade interface coupling method is proposed. Besides, the Craig-Bampton method is adopted to establish a reduced system for efficiency promotion. Then the central difference method is applied to solve the rubbing dynamic responses of the reduced system under the effects of different rotating speeds, disk unbalances, and disk positions. Finally, some main conclusions are summarized as follows: (1) In the disk-blade coupling region, three sets of node pairs rather than single node pair are of good accuracy in simulating the dynamic coupling characteristics of the blisk model via the comparisons of the modal results obtained from the experiment and the three-dimensional model in ANSYS; (2) when rubbing with the oval casing, the odd-multiple harmonics in the spectrum of the blisk and the even-multiple harmonics in that of the casing are prominent. Besides, the rubbing region on the casing is usually near the minimum casing radius but changes into the upper- or lower-half zone of the casing under a larger speed.